Ex Vivo Drug Screening Informed Targeted Therapy for Metastatic Parotid Squamous Cell Carcinoma - Nykänen, Noora; Mäkelä, Rami; Arjonen, Antti; Härmä, Ville; Lewandowski, Laura; Snowden, Eileen; Blaesius, Rainer; Jantunen, Ismo; Kuopio, Teijo; Kononen, Juha; Rantala, Juha K. (Frontiers in Oncology, 2021)
The purpose of ex vivo drug screening in context of precision oncology is to serve as a functional diagnostic method for therapy efficacy modelling directly on patient derived tumor cells. Here, we report a case study using integrated multiomics ex vivo drug screening approach to assess therapy efficacy in a rare metastatic squamous cell carcinoma of the parotid gland. Tumor cells isolated from lymph node metastasis and distal subcutaneous metastasis were used for imaging-based single cell resolution drug screening and reverse phase protein array-based drug screening assays to inform the treatment strategy after standard therapeutic options had been exhausted. The drug targets discovered on basis of the ex vivo measured drug efficacy were validated with histopathology, genomic profiling and in vitro cell biology methods and targeted treatments with durable clinical responses were achieved. These results demonstrate the use of serial ex vivo drug screening to inform adjuvant therapy options prior to and during treatment and highlight HER2 as a potential therapy target also in metastatic squamous cell carcinoma of the salivary glands.